New Bioactive Macrocyclic Diterpenoids from Euphorbia helioscopia. Issue 10 (4th October 2017) - Hua, Juan; Luo, Shi‐Hong; Liu, Yan; Liu, Yan‐Chun; Tan, Yan‐Yun; Feng, Ling; Xiao, Chao‐Jiang; Zhang, Ke‐Qin; Li, Sheng‐Hong; Niu, Xue‐Mei
Abstract : Three new macrocyclic diterpenoids, euphoscopoids A – C (1 –3 ), including two new jatrophanes and a new lathyrane, were isolated from the whole plant of Euphorbia helioscopia . Their structures were elucidated by spectroscopic methods. Antifeedant and cytotoxic activities of these isolates were evaluated. All compounds showed significant antifeedant activity against a generalist plant‐feeding insect, Helicoverpa armigera, with EC 50 values ranging from 2.05 to 4.34 μg/cm 2 . In addition, compound2 showed moderate cytotoxicity against tumor cell lines NCI‐H1975, HepG2, and MCF‐2, while compounds1 and3 were not active at 80 μm . The results suggested not only the defensive function of macrocyclic diterpenoids in E. helioscopia against insect herbivores, but also their potential applications as new natural insect antifeedants. Abstract :